Effectiveness of alternative dose fingolimod for multiple sclerosis. Issue 2 (April 2018) - Longbrake, Erin E.; Kantor, Daniel; Pawate, Siddharama; Bradshaw, Michael J.; von Geldern, Gloria; Chahin, Salim; Cross, Anne H.; Parks, Becky J.; Rice, Marc; Khoury, Samia J.; Yamout, Bassem; Zeineddine, Maya; et al.
Abstract : Background: Fingolimod is a daily oral medication used to treat relapsing multiple sclerosis (MS). Clinicians often adopt less frequent dosing for patients with profound drug-induced lymphopenia or other adverse events. Data on the effectiveness of alternate dose fingolimod are limited. Methods: We conducted a multicenter, retrospective, observational study at 14 sites and identified 170 patients with MS taking alternate doses of fingolimod for ≥1 month. Clinical and radiologic outcomes were collected and compared during daily and alternate fingolimod dosing. Results: Profound lymphopenia (77%), liver function abnormalities (9%), and infections (7%) were the most common reasons for patients to switch to alternate fingolimod dosing. The median follow-up was 12 months on daily dose and 14 months on alternate dose. Most patients (64%) took fingolimod every other day during alternate dosing. Disease activity was similar on alternate dose compared to daily dose: annualized relapse rate was 0.1 on daily dose vs 0.2 on alternate dose ( p = 0.25); proportion of patients with contrast-enhancing MRI lesions was 7.6% on daily vs 9.4% on alternate ( p = 0.55); proportion of patients with cumulative MS activity (clinical and radiologic disease) was 13.5% on daily vs 18.2% on alternate ( p = 0.337). Patients who developed contrast-enhancing lesions while on daily dose were at higher risk for breakthrough disease while on alternate dose fingolimod (odds ratio 11.4, p < 0.001). Conclusions: These data support the clinical strategy of alternate dosing of fingolimod in patients with good disease control but profound lymphopenia or other adverse events while on daily dose. Classification of Evidence: This study provides Class IV evidence that for patients with MS on daily dose fingolimod with adverse events, alternate dose fingolimod is associated with disease activity similar to daily dose fingolimod.